2020
DOI: 10.4330/wjc.v12.i9.450
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of prolonged chest pain in vasospastic angina

Abstract: BACKGROUND Patients with vasospastic angina (VSA) sometimes experience prolonged chest symptoms. The clinical characteristics of these patients have not been clarified. AIM To investigate the clinical characteristics of prolonged VSA patients. METHODS This study included 167 patients with VSA diagnosed by spasm provocation tests (SPTs) using acetylcholine, which recorded the frequencies of positive reactions to a low dose of acetylcholine (L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The left ventricular mass index (LVMI) was calculated using the formula of Devereux and Reichek [ 25 , 26 ]. As demonstrated previously [ 27 ], the flow-mediated dilation (FMD) and NTG-mediated dilation (NMD) of the brachial artery, which are objective measures of the endothelium-dependent and endothelium-nondependent functions, respectively, were evaluated using the UNEXEF device (UNEX Corp, Nagoya, Japan). Finally, peripheral endothelial function was measured via reactive hyperaemia peripheral artery tonometry (RH-PAT) using the Endo-PAT2000 device (Itamar Medical, Caesarea, Israel).…”
Section: Methodsmentioning
confidence: 99%
“…The left ventricular mass index (LVMI) was calculated using the formula of Devereux and Reichek [ 25 , 26 ]. As demonstrated previously [ 27 ], the flow-mediated dilation (FMD) and NTG-mediated dilation (NMD) of the brachial artery, which are objective measures of the endothelium-dependent and endothelium-nondependent functions, respectively, were evaluated using the UNEXEF device (UNEX Corp, Nagoya, Japan). Finally, peripheral endothelial function was measured via reactive hyperaemia peripheral artery tonometry (RH-PAT) using the Endo-PAT2000 device (Itamar Medical, Caesarea, Israel).…”
Section: Methodsmentioning
confidence: 99%
“…The kinds of adopted intracoronary modalities and/or the differences in the studied patients’ characteristics may contribute to the varied frequency of intracoronary thrombus formation. If patients with VA, a higher activity of VSA [ 22 , 32 ], were more frequently involved in the study, the frequency of intracoronary thrombus formation may have been higher, as shown in the study by Etsuda et al [ 10 ]. In the present study, under the condition that the spastic segments could be assessed using CAS, the frequency of intracoronary thrombus formation was 30% per patient and 26% per coronary artery, keeping with the results reported by others [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was asked about current smoking status, and any family history of coronary artery disease was recorded. Hypertension, dyslipidaemia, diabetes mellitus and chronic kidney disease were defined based on the standard definitions described in previous papers [ 22 ]. Blood chemical parameters were monitored routinely using blood drawn in the morning on CAG.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted an SPT utilising the procedures previously published [ 15 ]. Briefly, 20 and 50 µg of acetylcholine (ACh) were injected into the RCA following the initial CAG.…”
Section: Methodsmentioning
confidence: 99%
“…Small dosages of catecholamines were administered intracoronary or intravenously if the patient’s haemodynamics remained unstable. Low doses of ACh (L-ACh) were used in this study, with the RCA and LCA receiving 20 µg and 50 µg, respectively [ 15 ].…”
Section: Methodsmentioning
confidence: 99%